Gig Work and the Pandemic: Looking for Good Pay from Bad Jobs During the COVID-19 Crisis. Issue 1 (February 2023) - Reynolds, Jeremy; Kincaid, Reilly
COVID-19 led to work hour reductions and layoffs for many Americans with wage/salary jobs. Some gig work, however, which is usually considered precarious, remained available. We examine whether people doing gig microtasks right before the pandemic increased their microtask hours during COVID-19 and whether those changes helped them financially. Using data from workers on Amazon's Mechanical Turk platform from February, March, and April of 2020, we find that roughly one third of existing workers increased their microtask hours. Increases were larger for people who lost household income or wage/salary hours. Spending more time on microtasks, however, did little to help workers financially. Furthermore, the people most reliant on microtasks before the pandemic had worse financial outcomes than others. In short, even though microtask work might seem like a good way for people to recoup lost income during the pandemic, it was of limited utility even for the experienced workers in our sample.